Greed or Grievance? Linking Revenue Sharing Implementation to Unauthorised Resource Use and Conservation Support at Bwindi Impenetrable National Park - Twinamatsiko, Medard; Gumisiriza , Bugabo, Stephen; Kagoro-Rugunda, Grace (East African Nature and Science Organization, 2024)
Revenue sharing is considered a major incentive to promote Community Based Approaches to conservation of protected areas. The sharing of revenue from Protected Area resources is supported by conservationists to promote strong partnerships between protected area management and local communities to address unauthorised resource use for better conservation outcomes. This is premised on the ability of the shared revenue to translate into people’s livelihood improvement and minimize their dependency on resources from protected areas. However, empirical realities indicate that the practice of the Revenue Sharing policy barely addresses the initial objectives of human livelihood improvement to gain support for conservation. This study examined the Revenue Sharing Implementation, Data was collected from 715 respondents who included Local community members (including the unauthorised resource users), staff from conservation organisations in Bwindi and local council leaders. Data was collected using household survey questionnaires, key informant interviews and Focus Group Discussion (FGD). Results showed that most beneficiaries of the Revenue Sharing policy were random community households not the unauthorized resource users. The revenue sharing projects allocated to community members were majorly livelihood projects compared to common good projects. Projects included; livestock, passion fruit growing, poultry, provision of land and water projects. Unauthorised resource use was largely motivated by the need for bush meat, minor timber forest products especially firewood, collection of basketry materials and medicinal plants. Protected area managers ought to consider greater involvement of poachers in Revenue Sharing activities. Reducing unauthorized resource use requires systematic but also a combination of factors to mitigate the most driving forces that compel community members to engage in unauthorized forest resource use